THE EFFECTIVENESS OF SALESERA PRIVATE LTD. EMAIL MARKETING TO THE GROWTH OF CUSTOMER NUMBERS - Pradipta Kusumah, Kelana Ezra; Kusumawardhani, Amie (Diponegoro Journal of Management, 2023)
ABSTRACT SalesEra Private Ltd. is a startup that provides services in outsourcing, staffing, digital marketing, business development, IT support, and research reports. They are experts in competitive markets, accelerating expansion, and enhancing brand value. This research will provide SalesEra Private Ltd. with a solution to increase the effectiveness of email marketing and acquire more customers via email marketing as a marketing channel. Marketing is a social system enabling individuals and organizations to achieve their needs and wants by producing, distributing, and exchanging valuable goods and services. Email marketing is a targeted, personalized communication channel that entails sending marketing communications or information to a group of individuals via email and is one of the most effective means of communicating directly with consumers. Customization, information relevance, deliverability of emails, list quality, targeting, segmentation, customization, engagement, sender reliability, customization, relevance, interaction, and timing have been identified using research as crucial factors for the success of email marketing campaigns